Molecular detection of selected pathogens and their associated genes among Kelantan symptomatic hajj pilgrims - Ilia Eleena Mohd Baharin (2021)
Every year, many Malaysian Hajj pilgrims returning from pilgrimage show symptoms of respiratory tract infections. Many factors may lead to the occurrence of these symptoms among pilgrims, including breathing of polluted air, contact with infected people in overcrowded areas, and exposure to pathogens. Exposure to zoonotic pathogens is likely caused by animals that were sacrificed during the pilgrimage which can bear respiratory pathogens such as Mycobacterium bovis, Klebsiella pneumoniae, Streptococcus pneumoniae, Influenza A virus and Middle East Respiratory Coronavirus Syndrome (MERS-CoV). The involvement of zoonotic agents in respiratory infections among Malaysian Hajj pilgrims has yet to be investigated. Thus, the purpose of this research is to determine the prevalence of M. bovis, K. pneumoniae, S. pneumoniae, Influenza A virus and MERS-CoV among Kelantan Hajj pilgrims in 2016 who experienced symptoms of respiratory infections. A total of 189 participants joined this study after arriving at Sultan Ismail Petra Airport, Kelantan and their throat swab specimens were collected. 80 male pilgrims and 109 female pilgrims participated in this study. The mean age of the pilgrims was 56.52 ± 8.998 years. All pilgrims had one or more symptoms of RTIs. The common symptoms of the pilgrims were cough, sore throat, and fever. Nucleic acid extraction was performed from the swabs to screen for pathogens using polymerase chain reaction (PCR) and reverse-transcriptase PCR (RT-PCR) assays. Four pilgrims (2.11%) were positive for Klebsiella pneumoniae and 13 pilgrims (6.88%) were positive for Streptococcus pneumoniae. The presence of virulence genes and antibiotic resistance genes was also examined. In K. pneumoniae virulence gene detection, one of four samples respectively tested positive for the magA gene and K2A gene, and three positives for the rmpA gene. One of the 13 samples tested positive for S. pneumoniae lytA virulence gene. All samples were negative for S. pneumoniae virulence rrgA and pspC genes. Two of the four samples were positive for K. pneumoniae resistance genes blaKPC and blaOXA-48. None was positive for the K. pneumoniae blaNDM gene. For S. pneumoniae antibiotic resistance gene, 10 of the 13 samples were positive for mefA gene and seven of the 13 samples were positive for pbpA gene. There was no positive result for S. pneumoniae ermB gene. Therefore, there is no significant association between RTI symptoms experienced and the presence of pathogens in this study. This study also shows that small percentage of Hajj pilgrims experienced symptoms of respiratory tract infections associated with the presence of K. pneumoniae and S. pneumoniae in their throat swab specimens. The findings of this study may be preliminary data for future research of zoonotic infections among Hajj pilgrims.